Philosophical Analysis of the Meaning and Nature of Entropy and Negative Entropy Theories - Kun Wu; Qiong Nan; Tianqi Wu (Complexity)
The interpretation of entropy and negative entropy theories on the nature of information is the first scientific paradigm on the interpretation of the nature of information at the beginning of the rise of contemporary information science. The information entropy or negative entropy theories are the relative measurement for the structuralization degree of the system at a specific level, which have certain characteristics of relativity, functionality, and quantification. Although the concepts of entropy, negative entropy, information, entropy increase, and entropy decrease often have very different specific meanings in different disciplines and for different scientists, the meanings of these concepts are unified in essence and the differences between them are generated when the same kind of concepts is applied to the study of different directions of the same kind of phenomena: either to the static structuralization degree of the system or to the change of the dynamic structuralization degree of the system. Since entropy and negative entropy theories only measure the relationship of structural differences at a specific level of the system from a formal aspect, they are not aimed at the information itself but rather they are aimed at only the structuralization characteristics of the information carrier itself at a specific level. Because of this, it is impossible to deduce the general nature of information directly from such theories.